Cooling strategies to improve performance in the heat - Gavel, E. (SIRC, 2020)
Whether you are a high performance athlete training for the Olympic and Paralympic Summer Games in Tokyo, or a weekend warrior working on a personal best, learning to manage heat stress should be a priority. Heat stress and fatigue can lead to decreases in performance, influencing a podium finish, or can be the precursor to heat-related illness, which could end your competition all together. Therefore, it is important that athletes, sport scientists and practitioners have management strategy in place, especially when traveling abroad or competing in a hot environment.